Design, Sar, and Metabolism Study of Crucifereae Family Compound (Spirobrassinin) and its Analogs for Antiangiogenic Potential Targeting Hsp90 - Sharma, Neha; Faisal, Mohammad; Alatar, Abdulrahman A.; Khan, M Kalim A; Ahmad, Saheem; Akhtar, Salman (Current Proteomics, 2021)
Background: “Angiogenesis”, a major oncogenic signaling pathway, has been termed to be the most fascinating area of cancer therapy. Viewing this, the molecular chaperone Hsp90 has surfaced as a potential molecular target due to being vitally engrossed in sustaining stability, integrity, and functions of crucial proteins involved in multiple signaling pathways of tumor progression and metastasis. Objective: The study set sights on virtual screening (molecular docking and PreADMET study), MD simulation, and metabolism study of compounds from Crucifereae family along with the intensive structure-activity relationship studies in search of potent lead targeting HSP90. Methods: All the chemical structures were drawn using ChemDraw and converted into suitable 3D-structures. The target protein, HSP90 was retrieved from RCSB PDB. All the compounds of Crucifereae family and analogs were subjected to Lipinski’s rule of five and ADMET prediction using Molinspiration and PreADMET software respectively. The screened compounds were further exposed to MD simulation and metabolism studies. Conclusion: The docking results showed the promising inhibitory potential of Ana51 against Hsp90 with the binding energy of -11.32 kcal/mol as compared to its parent compound ‘spirobrassinin’ and a known inhibitor ‘Ganetespib’ exhibiting binding energy of -7.57 kcal/mol and -9.83 kcal/mol respectively. Optimization, flexibility prediction, and ascertaining the stability of Hsp90 in complex with the ligands were done by means of Molecular Dynamics (MD) simulations for 50 ns. The Hsp90-Ana51 complex exhibited stability with an RMSD value of 0.15 nm and Rg value to be 1.62 nm. The investigation further extends towards the SOM analysis of Ana51 to forecast the probable toxic and non-toxic in vivo metabolites via in silico tools (SMARTCyp, Xenosite Web, and PASS online server). Results: Ana 51 came out to be metabolically stable withstanding phase I metabolism and producing non-toxic metabolites compared to the parent compound and the standard drug. Obtained results propose Ana51 as a novel anti-Hsp90 lead compound with exceptional antiangiogenic capability.
Keywords: optimization